Children's hair cortisol and hair testosterone concentrations in response to environmental changes: from summer holidays to school. (2nd November 2021) - Schmid-Zalaudek, Karin; Fredriksen, Per Morten; Fabiani, Ester; Fredriksen, Maren V.; Brix, Bianca; Rössler, Andreas; Jantscher, Andreas; Goswami, Nandu
Abstract: Elevated hair cortisol concentrations in children have been linked to several stress-related conditions, including school-related demands. However, little is known about changes in hair testosterone in children. The present study investigated changes in hair cortisol and hair testosterone concentrations in the time course of four months – from summer holidays until mid of autumn of the following school year – in 60, 10–12-year-old (11.31 ± 0.63) school children (29 girls). Children's mental health was assessed by the strengths and difficulties questionnaire (SDQ) and related to hair cortisol and hair testosterone levels. Body mass index, waist-to-height ratio, and parental education were evaluated as potential confounders. In girls, the expected increase of hair cortisol concentrations was observed during school as compared to summer holidays, partly accounted for by peer- and emotional problems and the increase of HTC. In boys, hair cortisol and testosterone concentrations were significantly higher. Hair cortisol increased only slightly, while hair testosterone decreased significantly during school. The findings suggest a reciprocal influence of the hypothalamic-pituitary-adrenal and hypothalamic-pituitary-gonadal axis, differentially affecting girls' and boys' hormone production in response to environmental changes.